DETERMINANTS OF EMPLOYEE PERFORMANCE ON BANKING EMPLOYEES IN BATAM CITY - Sabri Sabri; Sumardin Sumardin; Amirullah Amirullah; Muhammad Fadli Luran; Rahman Syahputra (Jurnal Apresiasi Ekonomi, 2023)
The purpose of this study was to determine and analyze the effect of work stress, leadership style, and motivation on employee performance. The management of the organization must immediately look for and find out the reasons that cause decreased employee motivation. Based on observations, the results show that there are still employees who lack enthusiasm at work, work is sometimes sluggish, and do not respond well to the public when serving customers, it is suspected that this problem is due to a lack of employee motivation at work. The method used for sampling is the purposive sampling technique. The respondents used in this study were 100 employees who worked at state-owned banks in Batam. The results of this study indicate that the stress variable sometimes has no significant effect on employee performance. The leadership style variable partially has a significant effect on employee performance and the work discipline variable partially has a significant effect on employee performance. The variable ratio of work discipline, work stress, and leadership style is 66.5%, and the remaining 33.5 is influenced by other factors such as organizational culture, communication, etc. Based on the results of the F test, it can be interpreted that the variables of work discipline, work stress, and leadership style simultaneously have a significant effect on employee performance.